Indonesian education: A future promise - Roni Herdianto; Punaji Setyosari; Dedi Kuswandi; Aji Prasetya Wibawa; Andrew Nafalski; Ilham Mulya Putra Pradana (International Journal of Education and Learning, 2022)
Technological, social, and environmental changes are occurring globally. The disruption of technology will impact all sectors of human life. Sociocultural changes occur in the demographics and socioeconomics of the world population. During this chaotic condition, the Indonesian nation, with a large population and natural resources, must inevitably adapt to the global environment. Statistics Center Agency and World Bank data show that Indonesian student enrollment rates are rising, but preschool and tertiary gaps remain. Despite rising student enrollment, Indonesian education remains in crisis. One of the backbones of the nation's civilization to face global competition is good and mature planning in the education sector that adapts to global demands. This paper reviews the future of Indonesian education based on the mapping between Ki Hadjar Dewantara’s education model, the Indonesian education roadmap 2020-2015, the disrupted education model in 2020, The WEF Education 4.0 Framework, and the Future of the classroom model. This paper results in a future Indonesian education model framework to realize Indonesia's education vision for 2035.